1988
DOI: 10.1002/jcb.240380103
|View full text |Cite
|
Sign up to set email alerts
|

(2′‐5′)An‐dependent endoribonuclease: Enzyme levels are regulated by IFNβ, IFNγ, and cell culture conditions

Abstract: The levels of a (2'-5')An-dependent endonuclease (RNase L) were determined in extracts prepared from murine L cells and Ehrlich ascites tumor (EAT) cells by measuring specific binding of protein to a labeled derivative of (2'-5')An, (2'-5')A3[32P]pCp. RNase L levels were found to depend both on interferon (IFN) treatment and on cell growth conditions. Treatment of murine L cells and EAT cells with 100-2,000 IRU IFN beta or IFN gamma resulted in a similar 2-4-fold increase in the levels of RNase L when cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…RNase L is constitutively present in most types of cells (112), although treatment with IFN-␣/␤ enhances RNase L activity in some types of cells (111,182). Subsequent Northern blot analysis established that IFN-␣/␤ increases the steady-state amount of the RNase L transcript in mouse cells by about threefold (450).…”
Section: 5-oligoadenylate Synthetase and Rnase Lmentioning
confidence: 99%
“…RNase L is constitutively present in most types of cells (112), although treatment with IFN-␣/␤ enhances RNase L activity in some types of cells (111,182). Subsequent Northern blot analysis established that IFN-␣/␤ increases the steady-state amount of the RNase L transcript in mouse cells by about threefold (450).…”
Section: 5-oligoadenylate Synthetase and Rnase Lmentioning
confidence: 99%
“…The oligoadenylate synthetase (OAS)/RNase L pathway is another of the most extensively characterized. IFNαβ signaling stimulates synthesis of OAS and RNase L (Floyd -Smith, 1988), and once the cell is infected, viral double-stranded RNA (dsRNA) activates OAS to produce 2′5′-linked oligoadenylates (2′5′A). The 2′5′A then activate RNase L to degrade RNA, resulting in translation inhibition and blockade of viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…We suggested that intracellular constitutive RNase L could be activated by EV71 infection to degraded viral RNA. Previous studies have shown that RNase L is constitutively present in most types of cells ( Floyd-Smith and Denton, 1988 ), and treatment with IFN-α/β enhances RNase L activity in some types of cells ( Jacobsen et al., 1983 ; Floyd-Smith, 1988 ). We next demonstrated that EV71 infection could induce OAS3 but not RNase L expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%